2018
DOI: 10.1371/journal.ppat.1006909
|View full text |Cite
|
Sign up to set email alerts
|

Insect tissue-specific vitellogenin facilitates transmission of plant virus

Abstract: Insect vitellogenin (Vg) has been considered to be synthesized in the fat body. Here, we found that abundant Vg protein is synthesized in Laodelphax striatellus hemocytes as well. We also determined that only the hemocyte-produced Vg binds to Rice stripe virus (RSV) in vivo. Examination of the subunit composition of L. striatellus Vg (LsVg) revealed that LsVg was processed differently after its expression in different tissues. The LsVg subunit able to bind to RSV exist stably only in hemocytes, while fat body-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 53 publications
3
76
1
Order By: Relevance
“…A previous study showed that LsVg plays a pivotal role in mediating transovarial transmission of RSV . Recently, it was found that the only hemocyte‐produced Vg binding to RSV facilitated horizontal transmission in SBPH . Thus, we investigated the temporal expression profile of LsVg from naïve and RSV‐infected SBPH, and found that LsVg was highly expressed at the adult stage and had a higher expression in the viruliferous SBPH at 4 days post emergence.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A previous study showed that LsVg plays a pivotal role in mediating transovarial transmission of RSV . Recently, it was found that the only hemocyte‐produced Vg binding to RSV facilitated horizontal transmission in SBPH . Thus, we investigated the temporal expression profile of LsVg from naïve and RSV‐infected SBPH, and found that LsVg was highly expressed at the adult stage and had a higher expression in the viruliferous SBPH at 4 days post emergence.…”
Section: Discussionmentioning
confidence: 92%
“…The Vg ligand‐receptor pathway is considered critical for the mediation of RSV entry into SBPH ovaries. Knockdown of Vg or VgR transcript significantly decreased RSV titers and thus interfered with systemic virus infection . In addition, Vg or VgR was found to participate in the transmission of other pathogens …”
Section: Introductionmentioning
confidence: 99%
“…Building on our previous studies [28,29], we reveal that a plant arbovirus hitchhikes a well-defined insect ligandreceptor interaction pathway to achieve its cell entry. This represents a previously undescribed mechanism for the arboviral invasion of vector cells.…”
Section: Introductionmentioning
confidence: 74%
“…Thus, VgR is required for RSV to enter the nurse cells. When Vg is deficient and VgR remains normally expressed, RSV cannot efficiently invade the germarium [28,29], indicating that the influence of VgR on the ability of RSV to invade an ovary is dependent on Vg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation